Investigation of Antituberculosis Activity of Substituted Isoxazole Derivatives: A Combined Experimental and Molecular Docking Study - Anup Patil, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Tuberculosis (TB), caused by Mycobacterium tuberculosis, is a major global health concern, particularly due to drug-resistant strains. This study investigates substituted isoxazole derivatives for their antituberculosis activity through experimental and molecular docking approaches. The synthesized compounds were evaluated against the M. tuberculosis H37Rv strain, and molecular docking was used to predict their binding with enoyl-ACP reductase (InhA). Several compounds showed significant antituberculosis activity, with some surpassing the standard drug, isoniazid. This highlights the potential of isoxazole derivatives as new antituberculosis agents. Introduction: Tuberculosis (TB) remains a leading cause of death worldwide, worsened by the rise of drug-resistant strains. Isoxazole derivatives are known for various biological activities, making them candidates for new antituberculosis drugs. This study explores their synthesis, biological evaluation, and docking studies to assess their potential. Methods and Materials: Substituted isoxazole derivatives were synthesized via cyclization of β-keto esters with hydroxylamine hydrochloride. Structures were confirmed using NMR and mass spectrometry. The compounds were tested against M. tuberculosis H37Rv strain using the microplate Alamar Blue assay (MABA) to determine MIC values. AutoDock Vina was used to simulate the binding of isoxazole derivatives with enoyl-ACP reductase (InhA), analyzing binding affinities and interaction profiles. Results: Synthesis of the derivatives was successful, confirmed by spectroscopy. In vitro testing showed several compounds with MIC values between 0.5 to 8 µg/mL, with some outperforming isoniazid. Docking studies indicated effective binding to InhA, involving key interactions like hydrogen bonding and hydrophobic contacts. This suggests that these compounds inhibit InhA, correlating with their observed biological activity.